Gravitational torques of the dust penetrated stellar backbone of extragalactic spiral disks - Groess, Robert (My University, 2008)
“The nature of the nebulae and their place in the scheme of the universe have been favorite subjects of controversy since the very dawn of telescopic observations. In these later days, when the non-galactic nebulae have been clearly differentiated from the diffuse and the planetary, the discussion has concentrated around the spectacular forms of the spirals… island universes, scattered through the remote depths of space.” – Edwin P. Hubble It was only a mere 45 years ago, that some of the foremost astronomers such as Allan Sandage and Donald Lynden Bell believed that spiral galaxies were monolithic islands which were dynamically closed. This thesis has awaited the dawning of a new era wherein the disks of spiral galaxies can be “dust penetrated”. Prevalent ideas in the literature are overturned. Unprecedented images from IRAC onboard the Spitzer Space Telescope reveal the dynamic nature of nearby disk galaxies, including the two dominant spirals in our Local Group beyond the Milky Way. We show that M33 is a spiral galaxy whose disk grows outwards with time and which serves as a local Rosetta stone of a dynamically open system. We next show that the present-day morphology of M31 was induced only 210 million years ago. IRAC images betray its tumultuous recent past with the presence of two spectacular off-centre rings of dust, glowing at 8.0μm. A collision scenario seems most likely, with one of its larger satellite galaxies, M32. In our local universe, the bar phenomenon is ubiquitous. We separate bars from their parent disks in a sample of about 40 spiral galaxies, revealing that stronger spirals are not necessarily driven by stronger bars. Bars are not the universal excitation mechanism by which spiral structure is induced. Finally, surprising insights are gleaned from the IRAC 8.0μm window pertaining to the dust morphology of barred spirals. Three distinct form families of stellar bars are presented. May this thesis serve as “one small step for man” in our quest to expand our knowledge in the new epoch of quantitative galaxy classification in the dust-penetrated regime.
Keywords: Nebulae; Galaxies